Opportunities of Ukrainians' Adaptation in Germany and Positive German Experience Implementation in the Development of Social Programs in Ukraine - Khrystoforova, O. M.; Tatar, M. S.; Sergienko, O. A.; Babenko, M. V. (Inzhek publishing house, 2022)
Since the beginning of the war in Ukraine Germany is among the countries that have accepted the largest number of refugees from Ukraine. Despite the financial support of Germany to Ukrainian citizens, the solvency of Ukrainians, the sufficiency of their savings accumulated in Ukraine for living in Germany, the opportunities and problems for adaptation in Germany associated with the language barrier, the need for retraining of specialists in many specialties, problems for buying own housing in Germany, etc. remain a topical issue. The main indicators of the development of Germany and Ukraine, the comparison of living standards of the population in these countries, and the level of social security are considered in the article. The results of the study showed that the Ukrainian system of providing social assistance is imperfect, as there is no single Social Code, in contrast, there is an undeveloped institution of social inspection, and a low level of social benefits. At the same time, the level of protection of citizens in Ukraine is much lower than in Germany. In Ukraine, the wage level is not competitive. Ukrainians spend almost half of their income on the basic food needs. Therefore, there is no doubt that the post-war reconstruction of Ukraine should include both the necessary financing and the necessary reforms in Ukraine. The authors analyze the characteristic features of the German social assistance system, among which are: financing of the vast majority of social benefits at the expense of insurance contributions; unity and orderliness of social legislation; high level of development of the institute of social inspection, which is a guarantee for the objective assignment of social assistance; high level of social protection of refugees, which is a prerequisite for public peace and social stability; individual approach to the assignment of unemployment social assistance, which contributes to a lower level of unemployment compared to other European countries. The carried out research makes possible to substantiate the directions of the introduction of the German experience into the Ukrainian system of providing social services.

З початку війни в Україні Німеччина входить до числа країн, які прийняли найбільшу кількість біженців з України. Незважаючи на фінансову підтримку українським громадянам, що надаються Німеччиною, платоспроможність українців, достатність їх заощаджень, накопичених в Україні, для проживання в Німеччині, можливості та проблеми адаптації в Німеччині, пов’язані з мовним бар’єром, потребою в пошуку роботи, перепідготовці спеціалістів за багатьма спеціальностями, проблеми придбання власного житла в Німеччині тощо залишаються актуальними. У статті розглянуто основні показники розвитку Німеччини та України, здійснено порівняння рівня життя населення та рівня соціального забезпечення цих країн. Результати дослідження показали, що українська система надання соціальної допомоги є недосконалою, оскільки відсутній єдиний Соціальний кодекс, нерозвинено інститут соціального інспектування, низький рівень соціальних виплат. При цьому рівень захисту громадян в Україні значно нижчий, ніж у Німеччині. В Україні рівень оплати праці не є конкурентоспроможним. Майже половину своїх доходів українці витрачають на базові продукти харчування. Тому немає сумніву, що післявоєнна відбудова України повинна включати як необхідне фінансування, так і необхідні реформи. Проаналізовано характерні риси німецької системи соціальної допомоги, серед яких: фінансування переважної більшості соціальних виплат за рахунок страхових внесків; єдність і впорядкованість соціального законодавства; високий рівень розвитку інституту соціального інспектування, що є гарантією об’єктивного призначення соціальної допомоги; високий рівень соціального захисту біженців, що є передумовою громадського спокою та стабільності; індивідуальний підхід до призначення соціальної допомоги по безробіттю, що сприяє нижчому рівню безробіття порівняно із іншими європейськими країнами. Проведене дослідження дає змогу обґрунтувати напрямки впровадження німецького досвіду в українську систему надання соціальних послуг.
Можливості адаптації українців у Німеччині та впровадження позитивного німецького досвіду в розробці соціальних програм в Україні
Keywords: refugees; level of protection of citizens; social programs; provision of social services; Ukraine; Germany; біженці; рівень захисту громадян; соціальні послуги; фінансування; економічна діяльність